Single-cell chromatin accessibility of developing murine pancreas identifies cell state-specific gene regulatory programs - Sean de la O; Xinkai Yao; Sean Chang; Zhe Liu; Julie B. Sneddon (Elsevier, 2023)
Numerous studies have characterized the existence of cell subtypes, along with their corresponding transcriptional profiles, within the developing mouse pancreas. The upstream mechanisms that initiate and maintain gene expression programs across cell states, however, remain largely unknown. Here, we generate single-nucleus ATAC-Sequencing data of developing murine pancreas and perform an integrated, multi-omic analysis of both chromatin accessibility and RNA expression to describe the chromatin landscape of the developing pancreas at both E14.5 and E17.5 at single-cell resolution. We identify candidate transcription factors regulating cell fate and construct gene regulatory networks of active transcription factor binding to regulatory regions of downstream target genes. This work serves as a valuable resource for the field of pancreatic biology in general and contributes to our understanding of lineage plasticity among endocrine cell types. In addition, these data identify which epigenetic states should be represented in the differentiation of stem cells to the pancreatic beta cell fate to best recapitulate in vitro the gene regulatory networks that are critical for progression along the beta cell lineage in vivo.